ANALISIS PENYEBAB RESERVOIR RESISTIVITAS RENDAH PADA LAPISAN BATUPASIR FORMASI TALANG AKAR CEKUNGAN SUNDA ASRI DAN SUMATERA SELATAN - Octavia, Dea; Rian Cahya Rohmana; Widi Atmoko (Petro : Jurnal Ilmiah Teknik Perminyakan, 2024)
This research area is an oil and gas field characterized by low-resistivity zones in the Talang Akar Formation of the Sunda Asri and South Sumatra basins. The formation's lithology comprises sandstone, claystone, shale, and interspersed limestone, all deposited in a shallow marine environment. The objective of conducting petrophysical analysis is to identify the potential of the formation, particularly its low-resistivity reservoirs. The research utilizes well log, core, mud log, petrography, X-ray diffraction (XRD), and biostratigraphy data. Analysis of these data yields Gamma Ray logs, Resistivity logs, and Porosity logs, which include neutron log porosity (NPHI) and density porosity (RHOB). Several factors contribute to the low resistivity of reservoirs in this area, including the presence of clay minerals like kaolinite, chlorite, and illite in the Talang Akar formation, which interfere with low resistivity readings. The occurrence of conductive minerals such as pyrite, biotite, and tourmaline, the high salinity of formation water (>10,000 ppm), classified as High Saline Water, the fine to medium grain size of the sand (0.063 – 0.5 mm) which can retain formation water (irreducible water), leading to low resistivity readings, and the thickness of the rock layers, as evidenced by the depositional environment of the Talang Akar Formation, ranging from the upper delta plains to the lower delta plains, are also influential factors.